Cachexia and advanced dementia. Issue 2 (22nd February 2019) - Minaglia, Cecilia; Giannotti, Chiara; Boccardi, Virginia; Mecocci, Patrizia; Serafini, Gianluca; Odetti, Patrizio; Monacelli, Fiammetta
Abstract: Cachexia is a complex metabolic process that is associated with several end‐stage organ diseases. It is known to be also associated with advanced dementia, although the pathophysiologic mechanisms are still largely unknown. The present narrative review is aimed at presenting recent insights concerning the pathophysiology of weight loss and wasting syndrome in dementia, the putative mechanisms involved in the dysregulation of energy balance, and the interplay among the chronic clinical conditions of sarcopenia, malnutrition, and frailty in the elderly. We discuss the clinical implications of these new insights, with particular attention to the challenging question of nutritional needs in advanced dementia and the utility of tube feeding in order to optimize the management of end‐stage dementia.